JCC sebagai Komunikasi Digital Terpadu Informasi Kebencanaan di Jawa Barat - Fardiah, Dedeh; Darmawan, Ferry; Rinawati, Rini; Supaat, Viky Edya Martina; Abdullah, Sandi Ibrahim (Jurnal Komunikasi, 2023)
In the context of disaster communication in the digital era, synergy and cooperation between stakeholders in forming a disaster management information management system is carried out using digital communication integrated with the "Jabar Command Center" (JCC). However, the form of digital communication in the JCC is diverse because it covers all information about West Java. Therefore, this study aims to examine digital communication related to disaster information using the concept of integrated approach digital communication. The research method is a case study with data collection techniques through interviews and focus group discussions. The results showed that the form of digital communication in responding to disaster information in West Java was carried out by creating "Data Ecosystem Jabar," interactive public services through the website and the "SAPAWARGA" application. The communication pattern that occurred in the case of the Cianjur Earthquake is the complaint communication pattern through the Cianjur Earthquake Data Coordination Information Center (PISO DAPUR).